KEBIJAKAN PENGISIAN DIAGNOSIS UTAMA DAN KEAKURATAN KODE DIAGNOSIS PADA REKAM MEDIS DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Rohman, Hendra; Hariyono, Widodo; Rosyidah, . (Universitas Ahmad Dahlan, 2011)
Background: Policy about manage medical record had managed the system for reach order administration and improvement health services to show quality of hospital. New policy from Permenkes No.269/MENKES/PER/III/2008 make influence in this hospital policy because some policy using old government policy. At previously research, implementation that policy had many problem with some factor problem to fill in the main diagnose and the accurate code diagnose. The purpose of research is to know the policy to fill in the main diagnose and the accurate diagnose code at medical record in PKU Muhammadiyah hospital Yogyakarta. Method: This was non experiment research, this is deskriptif kualitatif and kuantitatif data as supporting to explain. The subject of research was internis, head of medical record, coder and documents medical record patient treatment internal disease at November 2008. Technique sampling for doctor internal disease, head of medical record, and coder was purposive sampling. But Technique sampling for documents medical record was simple random sampling. Kualitatif data tested validity with triangulasi. While for kuantitatif data the accurate diagnose code check using ICD-10. Result: The result of triangulasi identificated some factor problem to fill in the main diagnose and the accurate code diagnose. There is completeness documents medical record, busy, forget, lazy, not discipline, over burden work, patient APS, new terminology, difference perception, tools not support. The other policy most supporting that activity policy. Percentace to fill diagnose in the main diagnose from analyze 161 documents medical record is 71 (43,48%) to fill in and 91 (56,52%) not fill in. While the accurate code diagnose, from analyze 161 documents medical record have 237 code diagnose and 192 (81,01%) is accurate and 44 (18,99%) is not accurate. Conclusion: The policy most important for manage activity and communication between staff most supporting to result of policy implementation. Some factor problem can be overcome if all staff aware that policy is important and put into effect. Key word: Policy, Diagnose, Diagnose Code, Medical Record